Osteogenic Potential of Cultured Bone/Ceramic Construct: Comparison with Marrow Mesenchymal Cell/Ceramic Composite - Jin Iida; Takafumi Yoshikawa; Manabu Akahane; Hajime Ohgushi; Yoshiko Dohi; Yoshinori Takakura; Akitaka Nonomura (Cell Transplantation, 2004)
Osteogenesis occurs in porous hydroxyapatite (HA) when porous HA blocks combined with marrow mesenchymal cells are grafted in vivo. In vitro bone formation occurs in HA pores when HA combined with marrow cells is cultured in osteogenic medium containing dexamethasone. This cultured bone/HA construct possesses higher osteogenic ability when it is grafted in vivo. In the present study, we compared the osteogenic potential of a cultured bone/HA construct with that of a marrow mesenchymal cell/HA composite. Marrow cells were obtained from the femoral bone shaft of 7-week-old, male Fischer 344 rats and were cultured in T-75 flasks. Cells were concentrated, then frozen and stored in liquid nitrogen for 6 months. The cryopreserved cells were then thawed and prepared for subculture in porous HA (5 × 5 × 5 mm, Interpore 500) and for implantation with porous HA. After 2 weeks of subculture, three cultured bone/HA constructs were separately implanted in the right side of the back of each syngeneic 7-week-old male Fischer rat, and three thawed cell/HA composites (without subculture) were separately implanted in the left side. These implants were harvested at 2 or 4 weeks postimplantation, and prepared for histological, biochemical, and genetic analysis. Alkaline phosphatase activity and osteocalcin content of cultured bone/HA constructs were much higher than those of the cell/HA composites at 2 and 4 weeks postimplantation. Histological examination and gene expression data agreed with these findings. The culture technique discussed herein should facilitate the development of biosynthetic bone implants with higher osteogenic capacity.